Processing Recycled Brass Plate into Jewellery in Small and Medium Industries (SMEs): Medividi - Putri, Fauzia Trivana; Permanasari, Maharani Dian (Universitas Pembangunan Jaya, 2025)
This research aims to process brass metal waste into jewelry accessories through collaboration with Medividi SMEs. In the midst of increasing public concern for the environment, waste management, including metal waste, is an important issue because this waste is known as a pollutant with varying levels of toxicity that can damage the ecosystem. A form exploration approach with design thinking methods was used to maximize the processing of brass metal waste. The waste is processed into jewelry and other fashion accessories through various innovative material processing techniques, so as to increase the use value of brass waste, especially in Small and Medium Industries. The design thinking method is highly relevant in this context as it offers a systematic approach through the stages of empathy, definition, ideation, prototyping and testing. These stages help the design process to be more effective, starting with understanding the problem to generate new preferences in the creation of jewelry designs. The result of this research is brass waste-based jewelry with an innovative design, not only as an effort to recycle materials but also to bring aesthetic value.